The economics of enlargement - Manzocchi, Stefano (Palgrave Macmillan, 2003)
In this volume, well-known scholars examine the challenges facing the EU at the start of the Eastern enlargement, whose first wave should be decided at the end of 2002 and implementation in 2004-2006.